Artefact formation of formaldehyde in milk powders: Impact of analytical conditions. (November 2018) - Bessaire, Thomas; Savoy, Marie-Claude; Tarres, Adrienne; Mujahid, Claudia; Goldmann, Till; Perrin, Irène; Mottier, Pascal
Abstract: Formaldehyde (FA) was analyzed in milk powders by isotope dilution LC-MS/MS using 2, 4-dinitrophenylhydrazine (DNPH) as the derivatization agent. Analytical conditions (temperature and time) applied for derivatization were shown to strongly impact the levels of FA detected in micronutrient-fortified milk powders. In particular, vitamin C and ferrous iron catalyzed FA formation when derivatization was conducted at 60 °C, as described by several authors. Artefact formation of FA was demonstrated in a model study using 2 H2 -glycine and a freeze-dried raw cow's milk with added micronutrients. A limited survey of commercial fortified milk powders showed that FA levels were about 4-fold lower when analyses were conducted at room temperature as compared to 60 °C (0.65 ± 0.25 mg/kg and 2.57 ± 0.51 mg/kg, respectively). Based on data obtained at room temperature, FA exposure from fortified milk powders does not represent a safety concern even under worst-case assumptions. This study highlights the need and importance of adopting an international standard for FA analysis in foods. Highlights: Formaldehyde was analyzed by isotope dilution LC-MS/MS after DNPH derivatization. Iron and vitamin C may catalyze artefact formation of formaldehyde during analysis. Formaldehyde exposure from fortified milk powders is not a safety concern. An international standard for formaldehyde analysis in food is highly desirable.